2012
DOI: 10.11599/germs.2012.1009
|View full text |Cite
|
Sign up to set email alerts
|

Entecavir as specific antiviral therapy in selected cases of severe acute hepatitis B

Abstract: The role of specific antiviral treatment in severe acute hepatitis B has been subject to debate during the past few years. We present clinical findings in a series of three cases of severe acute hepatitis B and one case of acute hepatitis B treated with entecavir during 2007-2009, with interesting evolution. Entecavir appeared to improve the clinical evolution in the reported cases. Two of the patients displayed HBsAg to HBsAb seroconversion while another patient went into an inactive HBsAg carrier state. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…First, the prevalence of the infection in the general population and within the patient population served by the healthcare facility needs to be assessed. According to the CDC, 6 Romania is considered an intermediate-risk country for HBV, 7,8 with a 2-7% prevalence of chronic infection, 6 which is concordant with the results of a recent local epidemiologic study, pointing to a prevalence of 5.59%. 9 The same study found a 4.56% prevalence of HCV infection, 9 slightly higher than that recorded in another Romanian nationwide survey (3.23%).…”
supporting
confidence: 58%
“…First, the prevalence of the infection in the general population and within the patient population served by the healthcare facility needs to be assessed. According to the CDC, 6 Romania is considered an intermediate-risk country for HBV, 7,8 with a 2-7% prevalence of chronic infection, 6 which is concordant with the results of a recent local epidemiologic study, pointing to a prevalence of 5.59%. 9 The same study found a 4.56% prevalence of HCV infection, 9 slightly higher than that recorded in another Romanian nationwide survey (3.23%).…”
supporting
confidence: 58%
“…New methods that manage to overcome limitations and respond to challenges posed by special populations (including patients with concomitant infections such as hepatitis B, 64 hepatitis C, HIV, 65 or with hematologic malignancies) will definitely be well received.…”
Section: Resultsmentioning
confidence: 99%
“…29 Hepatitis viruses, particularly hepatitis A virus (HAV) 30 and hepatitis E virus (HEV) 31 can also contaminate milk and a relatively recent study has demonstrated that increased fat content of dairy products appears to contribute to the heat stability of HAV. 30 Hepatitis B virus (HBV) 32,33 or hepatitis C virus (HCV) pose less of a threat since they recognize parenteral transmission, without a fecal-oral route.…”
Section: Bacterial Infectionsmentioning
confidence: 99%